KAJIAN HUKUM PIDANA TERHADAP BATAS WAKTU PROSES PELAPORAN DALAM TINDAK PIDANA SAMPAI DENGAN DILAKUKANNYA PENYIDIKAN - Borti Rovendra; Philip A. Khana; Wirna Rosmely (UNES Journal of Swara Justisia, 2019)
The investigation process is a preliminary investigation carried out by the investigator as the first step of an investigation, whose purpose is to determine whether or not an investigation is possible. The research characteristic is descriptive analysis with normative juridical approach and with data source used is secondary data. The result of the research shows: firstly, the absence of deadline of the process of commencement of reporting up to the stage of investigation both in Criminal Procedure Code, Police Law, and Police Regulation on Management of Investigation of Crime, the absence of regulation, so that the birth of KUHAP, the law criminal act has deviated with the application of the principle of fast, simple and low cost. Second, the arrangement of deadline for criminal reporting process up to the investigation of countries in the AngloSaxon system such as the United States and countries that adhere to Continental European system such as the Netherlands did not manage for criminal reporting until investigation. thirdly, due to the absence of timeliness of criminal reporting process up to investigation in KUHAP, the Law on Police, and Perkap on Management of Criminal Investigation has violated the rights of each individual, both reporting and reporting parties that will reported.